Tau Protein and Its Role in Blood–Brain Barrier Dysfunction - Michalicova, Alena; Majerova, Petra; Kovac, Andrej (Frontiers in Molecular Neuroscience, 2020)
The blood–brain barrier (BBB) plays a crucial role in maintaining the specialized microenvironment of the central nervous system (CNS). In aging, the stability of the BBB declines and the permeability increases. The list of CNS pathologies involving BBB dysfunction is growing. The opening of the BBB and subsequent infiltration of serum components to the brain can lead to a host of processes resulting in progressive synaptic, neuronal dysfunction, and detrimental neuroinflammatory changes. Such processes have been implicated in different diseases, including vascular dementia, stroke, Alzheimer’s disease (AD), Parkinson’s disease, multiple sclerosis, amyotrophic lateral sclerosis, hypoxia, ischemia, and diabetes mellitus. The BBB damage is also observed in tauopathies that lack amyloid-β overproduction, suggesting a role for tau in BBB damage. Tauopathies represent a heterogeneous group of around 20 different neurodegenerative diseases characterized by abnormal deposition of the MAPT in cells of the nervous system. Neuropathology of tauopathies is defined as intracellular accumulation of neurofibrillary tangles (NFTs) consisting of aggregated hyper- and abnormal phosphorylation of tau protein and neuroinflammation. Disruption of the BBB found in tauopathies is driven by chronic neuroinflammation. Production of pro-inflammatory signaling molecules such as cytokines, chemokines, and adhesion molecules by glial cells, neurons, and endothelial cells determine the integrity of the BBB and migration of immune cells into the brain. The inflammatory processes promote structural changes in capillaries such as fragmentation, thickening, atrophy of pericytes, accumulation of laminin in the basement membrane, and increased permeability of blood vessels to plasma proteins. Here, we summarize the knowledge about the role of tau protein in BBB structural and functional changes.